Mrs. Roosevelt's gown, I presume - Knight-Sinner, Jan, author; Coloradoan, publisher (Colorado State University. Libraries, 1989)
Newspaper article clipping from The Coloradoan regarding a program featuring costume conservator and CSU alum, Polly Willman (’74 BS textile science, ’79 MS historic costume preservation).
Keywords: Fashion -- History; Fashion -- Exhibitions